KETERAMPILAN KOMUNIKASI BARISTA: ANALISIS PADA “NGOPICIREBON” - Lestari, Aghnia Dian (Universitas Swadaya Gunung Jati, 2023)
The increasing number of coffee consumption in the community makes coffee shops need credible baristas who have obtained learning qualifications, have experience and knowledge of coffee, and even use machines. Communication skills, such as the soft and hard skills of the Baristas, become the centre of the point. The method used is qualitative with symbolic interaction theory. The study results are an understanding of the communication skills of baristas, such as soft and hard skills, according to ngopicirebon and coffee consumers. The results of this study indicate that there are many skills that baristas must understand, including punctuality, proximity to consumers, hospitality, coffee taste, communicativeness, and the use of coffee tools. They are always required to hone skills, especially communication, to create customer satisfaction. Baristas can process coffee with expertise and creativity to determine the enjoyment of coffee and its artistic taste or the beauty made in serving a cup of coffee that consumers can enjoy. Baristas need communication skills so that they are competent in their field. Keywords: barista, communication skill, ngopicirebon